Recent Advances in Big Data: Features, Classification, Analytics, Research Challenges, and Future Trends - Mahmood, Khalid; Rahmah, Mokhtar; Raza, Muhammad Ahsan; Raza, Binish (IJCSNS, 2020)
Dealing with big data at present involves several procedures, including storage, processing, indexing, integration, and governance; thus, it poses a major challenge to application developers and research scientists. The challenge increases when accurate results must be obtained for queries in decision-making and cognitive applications regarding various disciplines and industries. A variety of literature on big data is available. However, big data must still be understood through various aspects, such as features, classification, analytics, research challenges, and future trends. This study provides a deep understanding of big data features, classification, and manipulation. An improved understanding of big data analytics and recent research challenges is also provided. Additionally, future trends are discussed for researchers. In conclusion, a vision to wisely and accurately improve information retrieval or search is presented to make better decisions using big data.